Análise proteômica comparativa entre Paracoccidioides brasiliensis e Paracoccidioides americana - Portis, Igor Godinho (2019)
The genus Paracoccidioides comprises termo dimorphic fungi that cause paracoccidioidomycosis, the most prevalent systemic mycosis in Latin America. These fungi can grow in yeast at 36 ° C and mycelium at temperatures below 28 ° C. Studies have shown that the fungus Paracoccidioides has molecular differences that allow the classification of species. Initially those fungi were classified in a single species, Paracoccidioides brasiliensis, but with the advancement of some molecular and genomic biology techniques, Paracoccidioides is currently classified into five species, P. lutzii, P. brasiliensis, P. americana, P. restrepiensis and P. venezuelensis. However, different species may have different proteomes and cellular responses. In this way in our study, we performed proteomic analyzes of two species of Paracoccidioides, P. americana and P. brasiliensis. iTRAQ labelling and mass spectrometery allowed the identification of 387 statistically significant proteins; two hundreds and two in P. brasiliensis and 111 proteins in P. americana. The identified proteins have different functions, such as amino acid metabolism, energy, cell defense, among others. The results showed differences in protein responses between P. americana and P. brasiliensis in proteins related to cell defense, mitochondria and energy metabolism, suggesting that these fungi may have different metabolism and pathways for growth, profliferation and virulence.